Mapalus dalam Pembangunan Kesehatan Masyarakat Minahasa di Sulawesi Utara - Jeini Ester Nelwan (Universitas Sam Ratulangi, 2020)
Backgroud: Mapalus is one of the socio-cultural values in the Minahasa community. Other existing socio-cultural values such as Si Tou Timou Tumou Tou and Torang Samua Basudara. Mapalus is an embodiment of philosophy Si Tou Timou Tumou Tou. The purpose of this research was to describing the implementation of Mapalus in public health. Method: This research was a qualitative research. Model of this research was a case study. Result: The result of this research was showed that the implementation of Mapalus has been change from traditional models (mutual cooperation and assistance) to modern models. Conclusion: Mapalus has grown from the agricultural sector to the other sectors like social, economic, government, and health.